Properties of Torrefied U.S. Waste Blends - Xu, Zhuo; Zinchik, Stas; Kolapkar, Shreyas S.; Bar-Ziv, Ezra; Hansen, Ted; Conn, Dennis; McDonald, Armando G. (Frontiers in Energy Research, 2018)
Power generation facilities in the U.S. are looking for a potential renewable fuel that is sustainable, low-cost, complies with environmental regulation standards and is a drop-in fuel in the existing infrastructure. Although torrefied woody biomass, meets most of these requirements, its high cost, due to the use of woody biomass, prevented its commercialization. Industrial waste blends, which are also mostly renewable, are suitable feedstock for torrefaction, and can be an economically viable solution, thus may prolong the life of some of the existing coal power plants in the U.S. This paper focuses on the torrefaction dynamics of paper fiber-plastic waste blend of 60% fiber and 40% plastic and the characterization of its torrefied product as a function of extent of reaction (denoted by mass loss). Two forms of the blend are used, one is un-densified and the other is in the form of pellets with three times the density of the un-densified material. Torrefaction of these blends was conducted at 300oC in the mass loss range of 0-51%. The torrefied product was characterized by moisture content, grindability, particle size distribution, energy content, molecular functional structure, and chlorine content. It was shown that although torrefaction dynamics is of the two forms differs significantly from each other, their properties and composition depend on the mass loss. Fiber content was shown to decrease relative to plastic upon the extent of torrefaction. Further, the torrefied product demonstrates a similar grinding behavior to Powder River Basin (PRB) coal. Upon grinding the fiber was concentrated in the smaller size fractions, while the plastic was concentrated in the larger size fractions.